Uptake, delivery, and anticancer activity of thymoquinone nanoparticles in breast cancer cells - Fakhoury, Isabelle; Saad, Walid; Bouhadir, Kamal; Nygren, Peter; Schneider-Stock, Regine; Gali-Muhtasib, Hala (Journal of Nanoparticle Research, 2016)
Thymoquinone (TQ) is a promising anticancer molecule but its development is hindered by its limited bioavailability. Drug encapsulation is commonly used to overcome low drug solubility, limited bioavailability, and nonspecific targeting. In this project, TQ nanoparticles (TQ-NP) were synthesized and characterized. The cytotoxicity of the NP was investigated in nontumorigenic MCF-10-A breast cells, while the uptake, distribution, as well as the anticancer potential were investigated in MCF-7 and MDA-MB-231 breast cancer cells. Flash Nanoprecipitation and dynamic light scattering coupled with scanning electron microscopy were used to prepare and characterize TQ-NP prior to measuring their anticancer potential by MTT assay. The uptake and subcellular intake of TQ-NP were evaluated by fluorometry and confocal microscopy. TQ-NP were stable with a hydrodynamic average diameter size around 100 nm. Entrapment efficiency and loading content of TQ-NP were high (around 80 and 50 %, respectively). In vitro, TQ-NP had equal or enhanced anticancer activity effects compared to TQ in MCF-7 and aggressive MDA-MB-231 breast cancer cells, respectively, with no significant cytotoxicity of the blank NP. In addition, TQ and TQ-NP were relatively nontoxic to MCF-10-A normal breast cells. TQ-NP uptake mechanism was both time and concentration dependent. Treatment with inhibitors of endocytosis suggested the involvement of caveolin in TQ-NP uptake. This was further confirmed by subcellular localization findings showing the colocalization of TQ-NP with caveolin and transferrin as well as with the early and late markers of endocytosis. Altogether, the results describe an approach for the enhancement of TQ anticancer activity and uncover the mechanisms behind cell-TQ-NP interaction.
EVALuna2:33952